Policy Paradigms, Transnationalism, and Domestic Politics - Skogstad, Grace, 1948- (Book collections on Project MUSE., 2011)
Policy Paradigms, Transnationalism, and Domestic Politics offers a variety of perspectives on the development of policy paradigms -- the ideas that structure thinking about what can and should be done in a policy domain. In this collection, international experts examine how both transnational actors and domestic politics affect the structuring of these paradigms. As well as theoretical chapters, this volume includes six case studies showing ideas at work in a diverse range of policy domains from the recognition of same-sex unions to risk regulation of genetically modified organisms. These qualitative analyses show how transnational activities shape policy paradigms by building consensus on ideas about feasible and desirable public policies across authoritative decision-makers. Expertly researched and assembled, Policy Paradigms, Transnationalism, and Domestic Politics provides insight into the conditions under which different transnational actors can bring about changes in the core ideas that affect public policy development. -- Book Description from Website.